Effectiveness of Birthing Ball Exercises Therapy in Improving Labor Pain and Labor Outcomes: A Systematic Review - Uma Phalswal; Sujata Jha; Priyanshi Dixit; Raksha Yadav (Journal of Family and Reproductive Health)
Objective: We must treat every woman with respect and compassion during her childbirth, allowing her to choose how she wants to remember the experience. Midwives and nurses use birthing balls to reduce labor pain and enhance maternal comfort without an epidural. The aim of this systematic review was to critically evaluate the available evidences on the effect of birthing balls on labor pain and labour outcomes. Materials and methods: Studies identified through PubMed, Semantic Scholar, and Mendeley electronic databases to gather evidences with selected keywords. This review incorporated randomised controlled trials and quasi-experimental research studies that met specific, predefined inclusion criteria. The search generated 441 titles and abstracts, which were further filtered down to 29 publications that were possibly relevant. Out of those, eight studies met the inclusion criteria. Performed a quality assessment of the articles using the JBI quality assessment tool. Results: All of the included studies show labor pain on a 10-cm Visual Analogue Scale (VAS), and interventional groups reported significantly less labor pain in delivery compared to the control group without birth ball exercise. On labour outcome findings, the intervention group had a higher mean score of cervical dilation in 2 studies, quicker head descent in 3 studies, lower labor time in 4 studies, mother satisfaction throughout labor in 2 studies, and a preference for vaginal delivery in 2 studies. Conclusion: Clinical implementation of a birthing ball exercise during the process of labor is an effective intervention to reduce labor pain and improve labor outcomes.